2(x+2)+x=3(x-1)+9

Simple and best practice solution for 2(x+2)+x=3(x-1)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+2)+x=3(x-1)+9 equation:



2(x+2)+x=3(x-1)+9
We move all terms to the left:
2(x+2)+x-(3(x-1)+9)=0
We add all the numbers together, and all the variables
x+2(x+2)-(3(x-1)+9)=0
We multiply parentheses
x+2x-(3(x-1)+9)+4=0
We calculate terms in parentheses: -(3(x-1)+9), so:
3(x-1)+9
We multiply parentheses
3x-3+9
We add all the numbers together, and all the variables
3x+6
Back to the equation:
-(3x+6)
We add all the numbers together, and all the variables
3x-(3x+6)+4=0
We get rid of parentheses
3x-3x-6+4=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation

See similar equations:

| 7x+8x−8=3(5x+9) | | 9-2t=-3 | | -3m+25+m+21=3 | | 2x-4(x-5)=-4+2x+16 | | -2+2p=-6 | | 4a-7=4a-8+1 | | 8=3d+5 | | -33+7n=4(3n-2) | | 5-2c=-1 | | -7v+1=8 | | 1.33m+2=2.166 | | 39x+1,711x-44=35(50x+90) | | 175-x=238 | | -9.5x+0.73=-3.07 | | -7k+38=8(-5-4k)+3 | | 13y+(10y+24)=180 | | 3z−1=5 | | 9.6(a+5)=4.8a=81.6 | | 13u+29=5u-27 | | 9w+6=42 | | 12-9x=-3(x+100 | | x^2=(27/7)^2+36 | | 7+1/4x=8 | | 3(m+12)=24 | | 15=-9t-3 | | 15=5x=1-3x | | 5a-(6-a)=4a-18 | | 57=(x-9)+2x | | 15y(10y+24)=180 | | 4(8x-8)=-192* | | n^2=(27/7)^2+36 | | -15(a+3)=-55 |

Equations solver categories